2017
DOI: 10.1021/acssuschemeng.6b01744
|View full text |Cite
|
Sign up to set email alerts
|

Template Free Synthesis of Ni-Perovskite: An Efficient Catalyst for Hydrogen Production by Steam Reforming of Bioglycerol

Abstract: Ni-based perovskite catalysts are prepared by two different methods and used as selective catalyst for hydrogen production from glycerol. The physicochemical properties of the catalysts were studied by X-ray diffraction, H2 temperature-programmed reduction, NH3 temperature-programmed desorption, N2 physisorption and TEM analysis. The effects of perovskite structure on the Ni particle size and acidity were studied, and the possibility of a nontemplate approach is examined. Steam reforming of bio-glycerol was ca… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
28
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 54 publications
3
28
0
1
Order By: Relevance
“…The performance of the two best is attributed to the highly basic sites due to Ca and Sr dopants in La0.4Sr0.2Ca0.3Ni0.1Ti0.9O3-δ and the influence of the synergy due to Ni-Fe alloy in La0.5Sr0.4Fe0.1Ni0.1Ti0.8O3-δ in addition to the basic sites. The catalytic activity is comparable to what was reported by Ramesh and Venkatesha (2017) and Papaioannou et al (2019). The prevalence of the predominant gases is attributable to the exsolved nickel particles and rapid pyrolysis due to kinetic which has facilitated the gasification and oxidation of the glycerol carbonaceous decomposition products leading to the formation of CO as supported in related works (Wu et al, 2014;Ramesh and Venkatesha, 2017).…”
Section: Catalytic Activity As Demonstrated By the Catalyst Materialssupporting
confidence: 82%
See 1 more Smart Citation
“…The performance of the two best is attributed to the highly basic sites due to Ca and Sr dopants in La0.4Sr0.2Ca0.3Ni0.1Ti0.9O3-δ and the influence of the synergy due to Ni-Fe alloy in La0.5Sr0.4Fe0.1Ni0.1Ti0.8O3-δ in addition to the basic sites. The catalytic activity is comparable to what was reported by Ramesh and Venkatesha (2017) and Papaioannou et al (2019). The prevalence of the predominant gases is attributable to the exsolved nickel particles and rapid pyrolysis due to kinetic which has facilitated the gasification and oxidation of the glycerol carbonaceous decomposition products leading to the formation of CO as supported in related works (Wu et al, 2014;Ramesh and Venkatesha, 2017).…”
Section: Catalytic Activity As Demonstrated By the Catalyst Materialssupporting
confidence: 82%
“…The catalytic activity is comparable to what was reported by Ramesh and Venkatesha (2017) and Papaioannou et al (2019). The prevalence of the predominant gases is attributable to the exsolved nickel particles and rapid pyrolysis due to kinetic which has facilitated the gasification and oxidation of the glycerol carbonaceous decomposition products leading to the formation of CO as supported in related works (Wu et al, 2014;Ramesh and Venkatesha, 2017). Other contributing factor that might have influenced the observed catalytic behaviour is the reverse water gas shift reaction (RWGSR).…”
Section: Catalytic Activity As Demonstrated By the Catalyst Materialssupporting
confidence: 81%
“…The peaks observed at 724 and 711 eV corresponds to Fe 2p 1/2 and Fe 2p 3/2 respectively. The satellite peak at 718 eV confirmed that Fe exists in +3 oxidation state . The Peaks in Figure at 516 and 524 eV represent the V 2p 3/2 and V 2p 1/2 respectively, the characteristic peak of vanadium in +5 oxidation state.…”
Section: Resultsmentioning
confidence: 76%
“…The satellite peak at 718 eV confirmed that Fe exists in + 3 oxidation state. [19] The Peaks in Figure 5 at 516 and 524 eV represent the V 2p 3/2 and V 2p 1/2 respectively, the characteristic peak of vanadium in + 5 oxidation state. In Figure 5 the main peak at 529.5 eV corresponds to the O 1s lattice oxygen while the small hump at 531.6 eV represents the defect oxygen.…”
Section: Spectral Studiesmentioning
confidence: 99%
“…Perovskite-based catalysts were also tested for this application. For instance, LaNiO 3 tested at 650 °C led to 58 to 72% conversion, depending on the preparation method and conditions [ 53 , 54 ]. Moreover, when the Ni precursor was in the form of hydrotalcite, better performance and most of all stability was reported, attributing deactivation by coking to sintering of the Ni nanoparticles [ 17 ], in line with recent findings.…”
Section: Resultsmentioning
confidence: 99%